Full Service Carriers: An Analysis Of Strategic Responses By Full Service Carriers To The Threat Posed by Low Cost Carriers - Subramaniam, Lakshmanan (2007)
The last couple of years have proven to be very tough for the airline industry. Macroeconomic turmoil, such as the terrorist attacks of September 11, 2001, consequent worldwide economic recession, the lingering threat of terrorism, the SARS virus and the effects of the Iraq war have all had a combined drastic effect on both volumes and values of traffic in the airline industry. Microeconomic and industryrelated changes, most definitively the dramatic growth of market power of low cost carriers (LCCs), are haloing this condition of the airline environment, putting into deep crisis incumbents’ traditional business models and giving rise to liquidity losses, huge deficits and bankruptcies. In the US market, LCCs have been a reality since the early 1970s and have been counterattacked many times, with scarce luck, by incumbent network carriers or full service carriers (FSCs). In the European and Asian context, the LCCs’ attack is fresher and the jury is still out on the ultimate responses of the FSCs. After an introductory parenthesis on the rise of the low cost phenomenon in the airline industry, this paper aims to analyse the strategic responses of selected incumbents in the mature market of the United States as well as the maturing market of Europe and emerging market of South East Asia. This paper will analyse the main competitive and marketing strategies selected FSCs have adopted in coping with the huge wave of low-cost entities to survive in the current altered environment.